PENGARUH PENGALAMAN AUDITOR, TEKANAN WAKTU DAN INDEPENDENSI TERHADAP KUALITAS AUDIT DENGAN PEMODERASI SKEPTISME PROFESIONAL - Agustin, Ricy Dwi; Agoes, Sukrisno (Fakultas Ekonomi Universitas Tarumanagara, 2025)
Audit quality is still a challenge for the public accounting profession. Starting from this problem, the aim of the research is to determine the influence of the variables Auditor Experience, Time Pressure and Independence partially on Audit Quality; then to determine the role of the Professional Skepticism variable in strengthening/weakening the influence of Auditor Experience on Audit Quality, the influence of Time Pressure on Audit Quality, and the influence of Independence on Audit Quality. This research method is a quantitative method. The population is senior external auditors to partners at Public Accounting Firms (KAP) domiciled in DKI Jakarta. Sampling technique Data collection technique through surveys, by distributing questionnaires. Data analysis techniques include descriptive analysis, Partial Least Square-Structural Equation Modeling (PLS-SEM), and moderated regression. The research results show that Auditor Experience has a positive, but not significant, effect on Audit Quality; that Time Pressure has a positive but not significant effect; Independence has a positive and significant effect. Then Professional Skepticism significantly moderates (strengthens) the influence of Auditor Experience on Audit Quality; strengthens the influence of Time Pressure on Audit Quality, but is not significant; and strengthening the influence of Independence on Audit Quality. Than, Auditor Experience and Independence on Audit Quality are moderated by Professional Skepticism in line with grand theory, namely the theory of planned behavior. However, on the contrary, Time Pressure on Audit Quality is moderated. Professional Skepticism is not in line with grand theory, namely the theory of planned behavior.